The effect of corporate income tax on financial performance: Evidence from Palestine - Salem, Salem Mohammad Abdelaziz; Qutait, Zaid Rebhi Hammad (Journal of Economic, Administrative and Legal Sciences, 2023)
The purpose of this study is to investigate the corporate income tax effect on the financial performance of Palestinian firms. As Palestinian firms exist in an unstable situation and political risk with a fluctuating economy. It is worth studying to what extent the performance of these firms is affected by the corporate income tax (CIT) imposed by the Palestinian authority. This study is using panel data from 20 listed non-financial Palestinian firms during the period from 2016 to 2020. The random-effects model is used to empirically determine the effect of corporate income tax on financial performance after controlling for the most comprehensive macroeconomic factors, which have not been studied in the Palestinian context yet. This paper reveals a significant negative relationship between CIT and a firm’s performance. In contrast, the asset turnover ratio showed a significant positive relationship with financial performance. However, firm size is unrelated to financial performance, it shows up an insignificant relationship with the performance of Palestinian firms. This study proposes a further examination of the relationship between CIT and performance by extending empirical research on CIT performance determination using a different technique. This paper fulfills an identified need to study how an effective tax rate policy imposed in the Palestinian territory can sustain firms’ performance.
Keywords: corporate income tax; effective tax rate; size; financial performance; Palestinian firms